Pengembangan Usaha Koperasi Agar dapat Mengenal Pasar dan Pesaing - Dede Suleman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Cooperative business is certainly different from other types of financial companies, where the establishment process is based on principles, values, and norms that must be adhered to. Cooperative members are the owners of managed funds so that cooperatives must develop so that all members can enjoy the benefits which are ultimately aimed at the welfare of members. Developing cooperatives does not always run smoothly due to a lack of strategy or preparation. Cooperatives can run smoothly and develop if managed properly. The management of the duties of each member and the management of finances in the cooperative must be clear and neat. The types of strategies that can be chosen by cooperatives are broadly distinguished between corporate-level strategies and business unit-level strategies. The types of strategies that can be chosen at the corporate level include: single business, related business diversification, and unrelated business diversification or conglomeration. Meanwhile, the types of strategies that can be chosen at the business unit level include cost minimization, product differentiation, concentration on certain markets or a combination of the three. The problem experienced by the Mitra Armindo Jaya Cooperative is that the cooperative is relatively new, so it does not yet have an adequate understanding of cooperatives. The solutions offered in this activity, among others, provide an overview of how cooperative business development efforts are to be able to recognize the market and competitors so that existing business opportunities or opportunities can be utilized, and can overcome business obstacles that will interfere with the achievement of cooperative goals.